Pengembangan Sistem Informasi Petshop Pawarca Berbasis Web Menggunakan Metode Rapid Application Development (RAD) dan Black Box Testing - Arsa Anggun Anggraeni; Felista Argita Putri; Salsabila Mutiara Defa; Fajar Mahardika; Nur Muniroh; Cahya Vikasari (Universitas Al-Irsyad Cilacap, 2026)
Pawarca Petshop is a business engaged in the sale of pet products and grooming services. The processes of managing product data, sales transactions, grooming services, and delivering information to customers were previously conducted conventionally, resulting in inefficiencies in supporting business operations. This study aims to develop a web-based information system for Pawarca Petshop to improve data management efficiency and enhance customer service quality. The system was developed using the Rapid Application Development (RAD) method, which consists of the requirements planning, user design, construction, and cutover phases. This method was chosen because it enables faster system development through active user involvement throughout the development process. The developed system provides features for product management, grooming service management, service booking, sales transactions, and customer data management, all accessible through a web-based platform. System testing was conducted using the Black Box Testing method on 25 test scenarios covering all major system functionalities. The testing results showed that all scenarios were successfully executed according to the specified functional requirements, achieving a success rate of 100%. In addition, based on User Acceptance Testing (UAT) involving 10 respondents, the system achieved a user satisfaction score of 92.4%, indicating that it is easy to use and effectively meets the operational needs of Pawarca Petshop. The implementation of the system also reduced the average time required for transaction processing and data recording from 15 minutes to 5 minutes per transaction, representing an efficiency improvement of 66.7%. Based on the results of this study, the web-based Pawarca Petshop Information System developed using the RAD method successfully meets user requirements and improves the effectiveness and efficiency of business processes at Pawarca Petshop..